The Role of the State in Canadian Labour Relations. - Sack, Jeffrey; Lee, Tanya (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
The authors examine the role of the State in industrial relationsin Canada. They address themselves particularly to the questionsin which circumstances and to what extent the State shouldintervene.